A new species of the genus Pareiorhina (Teleostei: Siluriformes: Loricariidae) from the upper rio Parana basin, southeastern Brazil - Azevedo-Santos, Valter M. [UNESP]; Roxo, Fabio F. [UNESP] (Magnolia Press, 2015)
Pareiorhina pelicicei sp. n., a new Loricariidae, is described from the rio Grande, upper rio Parana basin, southeastern Brazil. The new species differs from its congeners by combination of the following characters: teeth with a minute lateral cusp; absence of small plates scattered on the thorax and abdomen; tip of the snout naked; lower predorsal length; higher number of premaxillary and dentary teeth.
Keywords: Taxonomy; Neotropical fishes; rio Grande basin; Stream fishes; South America